2007
DOI: 10.1128/aem.01117-07
|View full text |Cite
|
Sign up to set email alerts
|

Fate of the Two-Component Lantibiotic Lacticin 3147 in the Gastrointestinal Tract

Abstract: The component peptides of lacticin 3147 were degraded by ␣-chymotrypsin in vitro with a resultant loss of antimicrobial activity. Activity was also lost in ileum digesta. Following oral ingestion, neither of the lacticin 3147 peptides was detected in the gastric, jejunum, or ileum digesta of pigs, and no lacticin 3147 activity was found in the feces. These observations suggest that lacticin 3147 ingestion is unlikely to have adverse effects, since it is probably inactivated during intestinal transit.Lacticin 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 31 publications
2
27
0
1
Order By: Relevance
“…In another example, bacteriocinproducing cultures have also been shown in livestock to alter rumen flora and decrease shedding of bacterial pathogens (for a review see Diez-Gonzalez, 2007). The lantibiotics nisin and lacticin 3147 have both been shown to have anti-C. difficile activity (Bartoloni et al, 2004;Rea et al, 2007). However, in vivo studies showed that both these bacteriocins are degraded by digestive enzymes in the upper mammalian GIT.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In another example, bacteriocinproducing cultures have also been shown in livestock to alter rumen flora and decrease shedding of bacterial pathogens (for a review see Diez-Gonzalez, 2007). The lantibiotics nisin and lacticin 3147 have both been shown to have anti-C. difficile activity (Bartoloni et al, 2004;Rea et al, 2007). However, in vivo studies showed that both these bacteriocins are degraded by digestive enzymes in the upper mammalian GIT.…”
Section: Discussionmentioning
confidence: 99%
“…The peptides were then purified using RP-HPLC and the active fractions identified using MALDI-TOF MS as previously described (Rea et al, 2010). Biological activity was assessed using the WDA with C. difficile ATCC 59635 as the target organism (Rea et al, 2007).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations